Pengaruh Variasi Suhu pada Rotary Dryer terhadap Karakteristik Pengeringan Biji Kopi - Rudy Sutanto; I Gede Bawa Susana (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The use of a rotary dryer in the coffee bean drying process offers advantages in heating homogeneity and increased contact between the material and the drying medium. This study aims to analyze the effect of variations in the rotary dryer operating temperature on the drying characteristics of coffee beans in terms of changes in mass, moisture content, and drying rate. Experimental testing was conducted using four temperature levels, namely 40 °C, 50 °C, 60 °C, and 70 °C. The drying process lasted for 360 minutes with data collection intervals every 30 minutes to monitor the dynamics of moisture content reduction as a function of time. The results showed that increasing the rotary dryer operating temperature significantly accelerated the process of reducing the mass and moisture content of coffee beans. At a temperature of 70 °C, the rate of moisture reduction occurred the fastest compared to other temperature variations, while at a temperature of 40 °C the process was slower and tended to be stable. The drying rate showed a maximum value in the initial stage of drying, then decreased gradually as the moisture content in the material decreased. This phenomenon indicates a transition in the mass transfer mechanism from the dominance of free water evaporation to a slower internal moisture diffusion. Overall, temperature variations in rotary dryers significantly impact the drying dynamics of coffee beans. Determining the correct operating temperature is crucial for achieving optimal process efficiency while minimizing potential changes in material quality during drying.